2015
DOI: 10.1093/mnras/stv2365
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundance analysis of symbiotic giants – III. Metallicity and CNO abundance patterns in 24 southern systems

Abstract: The elemental abundances of symbiotic giants are essential to address the role of chemical composition in the evolution of symbiotic binaries, to map their parent population, and to trace their mass transfer history. However, the number of symbiotic giants with fairly well determined photospheric composition is still insufficient for statistical analyses. This is the third in a series of papers on the chemical composition of symbiotic giants determined from high resolution (R ∼ 50000), near-infrared spectra. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 109 publications
5
4
0
Order By: Relevance
“…Detailed photospheric abundance analysis for this system resulted in a slightly subsolar metallicity, [Fe/H] ≈ −0.5 and [α/Fe] = +0.27 (where α represents the average of the Mg, Si, and Ca elements), and an [α/Fe] versus [Fe/H] relation close to the mean one without any notable peculiarity to this object (Hinkle et al 2019). Similar α-element and Fe abundances were found in many symbiotic giants with white dwarf companions (Gałan et al 2016(Gałan et al , 2017. Bottom: the 15-50 keV daily-averaged count rate from the Neil Gehrels Swift BAT.…”
Section: Metallicitysupporting
confidence: 60%
“…Detailed photospheric abundance analysis for this system resulted in a slightly subsolar metallicity, [Fe/H] ≈ −0.5 and [α/Fe] = +0.27 (where α represents the average of the Mg, Si, and Ca elements), and an [α/Fe] versus [Fe/H] relation close to the mean one without any notable peculiarity to this object (Hinkle et al 2019). Similar α-element and Fe abundances were found in many symbiotic giants with white dwarf companions (Gałan et al 2016(Gałan et al , 2017. Bottom: the 15-50 keV daily-averaged count rate from the Neil Gehrels Swift BAT.…”
Section: Metallicitysupporting
confidence: 60%
“…Although N is also enhanced in the atmosphere of the red giant component of RS Oph ([N/H]=0.6±0.3), its moderate C/N=0.16 (Pavlenko et al 2008) indicates this N enhancement is not as strong as that in the nova ejecta. Systematic studies of photospheric abundances of a few dozens symbiotic giants revealed N/O 0.5 and C/N 0.2, and they are consistent with moderate enhancement of N and depletion of C as expected for their evolutionary stage (Ga lan et al 2016(Ga lan et al , 2017.…”
Section: Uv and Optical Spectroscopysupporting
confidence: 70%
“…The [α/Fe] versus [Fe/H] is close to the mean relation (Lambert 1987) and shows no notable peculiarity for this star. The α element and Fe abundances are similar to the abundances of many other SySt giants (Ga lan et al 2016(Ga lan et al , 2017. Casares et al (2017) report that in LMXB many of the low-mass stars show enhancements of Fe and α elements.…”
Section: Stellar Evolutionsupporting
confidence: 69%